2017
DOI: 10.1007/s12253-017-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

TFF3 Expression as Stratification Marker in Borderline Epithelial Tumors of the Ovary

Abstract: Borderline tumors (BOT) of the ovary account for 10% to 20% of ovarian neoplasms. Like ovarian cancer, BOT encompass several different histological subtypes (serous, mucinous, endometrioid, clear cell, transitional cell and mixed) with serous (SBOT) and mucinous (MBOT) the most common. Current hypotheses suggest low-grade serous carcinoma may develop in a stepwise fashion from SBOT whereas the majority of high grade serous carcinomas develop rapidly presumably from inclusion cysts or ovarian surface epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…El-Balat et al analyzed the expression of TFF3 in a cohort of 137 borderline tumors of the ovary (BOT): none of the serous and endometrioid BOT showed strong TFF3 expression. On the contrary, a higher TFF3 expression was found in BOT mucinous histology and BOT with mixed histology, suggesting a potential function of the protein in these histological subtypes [37]. Expression analysis of TFF3 was performed in a cohort of 91 OC patients by Hoellen et al No significant difference in TFF3 expression was found based on age, FIGO stage or residual tumor; meanwhile, a significant correlation of TFF3 expression and grade was detected [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Balat et al analyzed the expression of TFF3 in a cohort of 137 borderline tumors of the ovary (BOT): none of the serous and endometrioid BOT showed strong TFF3 expression. On the contrary, a higher TFF3 expression was found in BOT mucinous histology and BOT with mixed histology, suggesting a potential function of the protein in these histological subtypes [37]. Expression analysis of TFF3 was performed in a cohort of 91 OC patients by Hoellen et al No significant difference in TFF3 expression was found based on age, FIGO stage or residual tumor; meanwhile, a significant correlation of TFF3 expression and grade was detected [48].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have employed array-based genome-wide discovery platforms to identify aberrant mRNA expression and somatically acquired DNA sequence variants or mutations to determine the molecular changes underlying the development of OC and EC as a first step to identify molecular markers with potential clinical utility [33,34]. Using this technology, some proteins such as TFF3, Romo-1, NF-кB and SFRP4 have been identified as potential for diagnostic and prognostic targets in EC and OC [18,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result not only indicated that the development of SBOTs to invasive LGSOC involves a reduction in of p53 signal transduction but also suggested that p53 can inhibit the epithelial-mesenchymal transformation (EMT) process in SBOTs cells and thus the transformation to invasive ovarian cancer. El-Balat et al 66 further analyzed the expression of Trefoil factor-3 (TFF3) in 137 cases of BOT by immunohistochemistry and studied its relationship with histopathological characteristics. They found that the strong expression rate of TFF3 was 21.9% and there was no strong TFF3 expression in SBOTs and endometrial borderline tumors.…”
Section: Gene Expression and Pathways Alteration In Botsmentioning
confidence: 99%
“…On the other hand, TFF3 was highly expressed in 61.4% of MBOT (P < 0.001), suggesting that TFF3 potentially plays a role in MBOTs. 66 In addition, insulin-like growth factor II mRNA binding protein 3 (IMP3) is considered a prognostic marker of ovarian clear cell carcinoma. 67 El-Balat et al 68 analyzed the expression of IMP3 in 140 cases of BOT in a cohort and found that the expression of IMP3 was not related to the age of patients, FIGO stage, microinvasion, or the presence of implants, but was related to the mucinous subtype of BOTs (mucinous vs other subtypes, 42.2% vs 9.5%, P < 0.001).…”
Section: Gene Expression and Pathways Alteration In Botsmentioning
confidence: 99%